Home deaths of children under 5 years in rural South Africa: a population‐based longitudinal study. Issue 7 (14th May 2019) - Price, Jessica; Willcox, Merlin; Kabudula, Chodziwadziwa Whiteson; Herbst, Kobus; Kahn, Kathleen; Harnden, Anthony
Abstract: Objectives: To determine the proportion of under‐5 deaths that occurred at home in rural South Africa, whether care was sought prior to death, and determinants of home deaths amongst those who sought care. Methods: Verbal autopsy data were used for all under‐5 deaths, 2000–2015, in two health and demographic surveillance system sites. Trends in place of death and care‐seeking were assessed. Associations between sociodemographic factors and home death despite seeking care were assessed by multivariate logistic regressions. Results: There were 3760 under‐5 deaths; 1954 (53%) at home and 1510 (41%) in health facilities. Eighty‐four per cent of children who died at home accessed healthcare during their final illness. Amongst neonates for whom care was sought, those who were 8–27 days old were more likely to die at home than those who were 0–7 days old (OR = 5.56, 95%CI 2.69–11.55, P  < 0.001). Factors associated with home death of infants and young children despite seeking care included low maternal education (OR = 1.71, 95%CI 1.31–2.24, P  < 0.001), larger household size (OR = 1.56, 95%CI 1.17–2.06, P  = 0.002), traditional medicine use (OR = 2.33, 95%CI 1.75–3.12, P  < 0.001) and Mozambican descent (OR = 1.47, 95%CI 1.06–2.03, P  = 0.020). The proportion of HIV‐related deaths that occurred at home fell from 60% in 2008–2011 to 39% in 2012–2015 ( χ 2  = 13.86, P  < 0.001). Conclusion: More than half of under‐5 deaths in rural South Africa occurred at home although healthcare was sought for most children, highlighting that home deaths are not simply a function of poor care‐seeking. Interventions should target high‐risk sociodemographic groups. Abstract : Objectifs: Déterminer la proportion de décès d'enfants de moins de 5 ans survenus à domicile dans les zones rurales d'Afrique du Sud, si des soins ont été recherchés avant le décès et les déterminants des décès à domicile chez ceux qui ont recherché des soins. Méthodes: Les données d'autopsie verbale ont été utilisées pour tous les décès d'enfants de moins de 5 ans entre 2000 et 2015, dans deux sites du système de surveillance démographique et de santé. Les tendances en matière de lieu de décès et de recherche de soins ont été évaluées. Les associations entre les facteurs sociodémographiques et le décès à domicile malgré les soins recherchés ont été évaluées par des régressions logistiques multivariées. Résultats: Il y a eu 3.760 décès de moins de 5 ans; 1.954 (53%) à domicile et 1.510 (41%) dans les établissements de santé. 84% des enfants décédés à domicile ont eu accès à des soins de santé au cours de leur dernière maladie. Parmi les nouveau‐nés pour lesquels des soins ont été recherchés, ceux âgés de 8 à 27 jours étaient plus susceptibles de mourir à domicile que ceux âgés de 0 à 7 jours (OR = 5, 56; IC95% 2, 69‐11, 55; p <0, 001). Les facteurs associés au décès des nourrissons et des jeunes enfants à domicile malgré la recherche de soins comprenaient un niveau d'éducation maternelle faible (OR = 1, 71; IC95%: 1, 31‐2, 24; p <0, 001), une taille du ménage plus grande (OR = 1, 56; IC95%: 1, 17‐2, 06; p = 0, 002), l'utilisation de la médecine traditionnelle (OR = 2, 33; IC95%: 1, 75‐3, 12; p <0, 001) et l'origine mozambicaine (OR = 1, 47; IC95%: 1, 06‐2, 03; p = 0, 020). La proportion de décès liés au VIH survenus à domicile est passée de 60% en 2008‐2011 à 39% en 2012‐2015 (Chi 2 = 13, 86; p <0, 001). Conclusion: Plus de la moitié des décès des moins de 5 ans dans les zones rurales d'Afrique du Sud sont survenus à domicile bien que pour la plupart des enfants une recherche de soins de santé a été effectuée, soulignant que les décès à domicile ne sont pas simplement liés à un mauvais recours aux soins. Les interventions devraient cibler les groupes sociodémographiques à haut risque.